PENGEMBANGAN SISTEM FRONT END PADA PMTCINVENTORY BERBASIS MOBILE MENGGUNAKAN METODE WATERFALL - Izzati Muhimmah; Muhammad Khalifah Milano (Universitas Muhammadiyah Gresik, 2024)
The company inventory is one of the important aspects that receives primary attention in a company. Generally, companies with a vast and diverse inventory cater to clients and local employees. Therefore, company inventory becomes a primary concern for various businesses. However, in some companies, inventory tracking still relies on software such as Microsoft Word and Microsoft Excel. This makes the recording and management of company inventory less efficient. Based on this issue, it is concluded that companies need an electronic inventory system or e-inventory. Hence, the development of a mobile-based inventory system is undertaken. This development utilizes the Waterfall method and the Flutter framework. The stages in the Waterfall method include requirements, design, implementation, testing, and maintenance. The advantage of using this method is that the work is carried out gradually and systematically. The results of the research conducted using the Waterfall method include the creation of five pages or user interfaces: Dashboard, Login, Home, Saya, and Detail Alat. Each page has different functionalities. The user interface is created using the Flutter framework and tested using the black box testing method, resulting in alignment between user preferences and the application created.